(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The road network is critical to every country’s transportation and communication. The state of the pavement is one component in determining the effectiveness of the road network. Roads have a key role in economic development and progress, as well as providing significant social advantages. Overloading on roads is a severe problem in India and other developing countries across the world. Although the subject of vehicle overloading is not new, there has not been much debate about it in emerging nations. It is believed that more than half of the commercial trucks travelling on India’s national and state roadways are overcrowded. This is especially dangerous in places near mining operations. The carriers disregard and breach the regulatory axle load limitations and gross vehicle weight limits. The consequences of overloading are numerous. Newly constructed roads are subjected to accelerated loading circumstances, causing loads to surpass design limitations far before their intended life is over. As a result, roads collapse prematurely. The maintenance element gets complicated as a result of this feature, with the resulting fallout being poor road condition or high maintenance. Other negative consequences of overloading include higher road accidents, vehicle damage, slower speeds and inefficiency, delays in vehicular traffic, and congestion. A study was done to determine the root problems, and numerous suggestions were made.